The relationship between flexibility and some of the variables Albayukinmetekih cycle arm in swimming was 100 m - Saleh, Mohammed (Journal of Physical Education, 2007)
This stuely aim to show the relation ship between one of physical fitness (flilxabuty) and some the biomicancal parameters. This stuoly was a discraptive one, the sample was 16 swimers from Baghdad clcbs at the age of 13-14 years. Statiscal analysis were used to calculate the data such us meain, made, median, stander diviatien, and persan. The rearcher reached the following conclusions, for the Filixablity tests. The relling feet toward the legs have the most relatoms with the other tests, and it was(3) reloction ship. The rolling feet test have tow relation ship with the hand stroke and the length of this stroke. Joint and sholders Joints have tow relationships with performance and the number of stroks respactivly. The porameters of bioyeenimutic at arm circal the result show the following. The number of stroke volem have the most relationships, and it was(3). The frecquncy stoke parameter have Juist one relationship with the length of the stroke.